Gold substitution in mercury cuprate superconductors - Bordet, P; Le Floch, S; Capponi, J; Chaillout, C; Gorius, M; Marezio, M; Tholence, J; Radaelli, P (1996)
By using the high-pressure high-temperature technique, we succeeded in substituting in the mercury cuprate superconductors up to about 40% of mercury by gold. The samples were studied by X-ray and neutron powder diffraction, electron microscopy, energy dispersive spectroscopy. AC suceptibility measurements were also performed. The experimental data obtained for the Au substituted Hg-1223 compound indicate that the substitution leads to overdoping of the CuO2 layers, with a progressive decrease of cell parameters and Tc with increasing gold content. Taking into account these results, we used gold substitution to increase Tc of a Hg-1245 sample up to 110 K. The corresponding unsubstituted samples are normally obtained by the high-pressure high-temperature technique in an underdoped state with a Tc around 100 K.